2023
DOI: 10.38142/ijesss.v4i2.591
|View full text |Cite
|
Sign up to set email alerts
|

Performance Effectiveness Based on Accounting Information Systems in The Framework of Tourism Villages in Bali

Abstract: Performance is the level of success of a person as a whole at a certain time in carrying out a task. Performance has the most important role, if performance decreases, it will gradually threaten the company and result in the company going bankrupt. Based on the phenomena and results of previous studies, the accounting information system is a component that can be streamlined to improve performance. Apart from Accounting Information Systems, accounting knowledge is considered very important for the Company. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Additionally, AIS increases the strategic approach to business and organizational capabilities (Hlongwane, 2023). Dewi and Anggiriawan (2023) found that the use of accounting systems has been shown to improve their performance. Overall, AIS can enhance performance via support, formalization, user cooperation, technical knowledge, and strategic management of business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, AIS increases the strategic approach to business and organizational capabilities (Hlongwane, 2023). Dewi and Anggiriawan (2023) found that the use of accounting systems has been shown to improve their performance. Overall, AIS can enhance performance via support, formalization, user cooperation, technical knowledge, and strategic management of business.…”
Section: Literature Reviewmentioning
confidence: 99%